Identifying and Mapping the Key Challenges of Water in Sudan to Accelerate the Achievement of SDG6 - Abdelgalil, Eltigani Bashier; Hagr, Elharith A A (Gezira Journal of Engineering and Applied Sciences; Vol 19 No 1 (2024), 2026)
Sudan faces a complex nexus of water-related challenges that severely impede progress toward Sustainable Development Goal 6 (SDG 6) targets. Achieving Sustainable Development Goal 6 (SDG 6), which aims to ensure the availability and sustainable management of water and sanitation for all, remains a major challenge in Sudan due to persistent water scarcity, uneven distribution of resources, infrastructure degradation, climate variability, and socio-political instability. This study aimed to identify, classify, and spatially map the most serious water-related challenges across Sudan to support evidence-based decision-making and accelerate progress toward SDG 6. Despite possessing substantial potential water resources, Sudan's progress toward achieving SDG 6 by 2030 is severely hindered by a lack of integrated data on national water challenges and a failure to prioritize targeted, sustainable interventions. Data were collected from 300 stakeholders across 10 states in Sudan, supported by GPS-based mapping of water challenge locations and community validation. Data collection combined precipitation and LULC, water scarcity, stakeholder field surveys, and targeted point-source water salinity. These multi-tiered datasets were spatially integrated using ArcGIS overlay analysis and correlation tests to assess relationships among physical, institutional, and key water challenges.. The findings indicate that North Kordofan, Red Sea, White Nile, Kassala, and Gadarif experienced the highest levels of water scarcity. Additionally, elevated water salinity is most prevalent in the Red Sea, White Nile, Gedarif, and Gezira states. Positive correlations were observed between salinity and water scarcity (r = 0.319, p < .001), perceived intensive extraction of groundwater and water scarcity (r = 0.198, p < 0.001), and between perceived intensive extraction of groundwater and salinity (r = 0.161, p < .005). These results suggest that higher salinity and groundwater over extraction are linked to increased water scarcity. The findings provide spatially explicit evidence to guide policymakers in prioritizing sustainable water management interventions towards achieving SDG 6 and related SDGs.